Solidifikát z nebezpečného odpadu a možnosti jeho uvedení na trh - Hodul, Jakub (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Diplomová práce se zabývá možností využití technologie solidifikace pro transformaci nebezpečných odpadů se záměrem dosáhnout materiálového využití produktů solidifikace – solidifikátů. Cílem této práce je nalézt vhodnou recepturu pro solidifikát z nebezpečného odpadu, která zaručí takové vlastnosti solidifikátu, jež umožní jeho uvedení na trh.

Diploma thesis deals with the possibility of using solidification technology to transform the hazardous waste with the aim to achieve the material utilization of solidification products. The aim of the thesis is to determine a suitable solidification formula for solidification product made of hazardous waste that will ensure properties of the solidification product, those will allow its placing on the market.
Solidification product made of hazardous waste and possibilities of its launch to the market
Keywords: Nebezpečný odpad; neutralizační kaly; solidifikace; využití solidifikátu; solidifikační činidla; kontaminanty; životní prostředí; skládka odpadu; ekologické požadavky; fyzikálně-mechanické požadavky; mikrostruktura; certifikace; solidifikační technologická linka; Hazardous waste; neutralizing sludge; solidification; solidification product utilization; solidification agents; contaminants; environment; waste landfill; environmental requirements; physical and mechanical requirements; microstructure; certification; solidification technological line